Receptors and host factors: key players in human metapneumovirus infection - Dong, Yingdong; Xie, Zhengde; Xu, Lili (Frontiers in Cellular and Infection Microbiology, 2025)
Human metapneumovirus (hMPV) is a significant global pathogen that causes acute respiratory tract infections, especially in infants, young children, the elderly, and immunocompromised individuals. Despite its increasing prevalence, there are currently no vaccines or effective treatments available for hMPV. The pathogenesis of hMPV infection is a complex process involving a multitude of host factors and viral receptors. These interactions determine the virus ability to enter host cells, replicate, and evade the immune response. This review is the first to provide a comprehensive overview of the current understanding of host–virus interactions in hMPV pathogenesis. By elucidating these mechanisms, we can identify potential targets for antiviral drugs and improve the management of hMPV infections.